Nedim’in şiirlerinde ‘Vâsûht’ tarzı aşkın izleri - (:unkn) unknown (My University, 2019)
Divan şiiri aşk anlayışının iki önemli öznesi olan âşık ile mâşuk, şiirde birbirinden farklı özelliklerlekarşımıza çıkmaktadır. Divan şiiri dünyasında pâdişâh, sultan, şâh gibi kelimelerle nitelenen veâşıklarına sürekli cefa çektirip zulmeden mâşuk karşısında ona tek taraflı bir aşkla bağlanıp sevgilininzulmüne katlanan, dahası bundan zevk alan bir âşık tipi yer almaktadır. Ancak şiire hâkim olan buaşk anlayışında özellikle klasik sonrası dönemde bazı değişimlerin yaşandığı, sevgilinin cefasınakatlanmak istemeyen ve ondan yüz çeviren bir âşık tipinin şiirde kendine yer bulmaya başladığıgörülmektedir. Divan şiiri aşk anlayışındaki bu değişimde, 16. asır İran edebiyatında gelişmeyebaşlayan Vâsûht tarzı aşkın etkileri olduğu göze çarpar. Sevgilinin cefasına katlanmamak, ondannefret edip yüz çevirmek şeklinde karşımıza çıkan Vâsûht tarzı aşk anlayışına, zaman zaman klasikdönem divan şairlerinin şiirlerinde de rastlanmaktadır. Ancak özellikle 18. asırdan itibaren bu aşkanlayışının divan şiirinde daha belirgin bir şekilde karşımıza çıktığı söylenebilir. Şiirlerinde Vâsûhttarzı aşka yer veren şairlerden biri de Nedim’dir. Onun şiirleri çoğunlukla gerçek hayattan alınmışkonulara ve sevgililere yer verir ve bu şiirlerdeki aşk anlayışı, çoğu zaman divan şiirindeki hâkimsöylemle örtüşür. Ancak şairin bazı şiirleri ve beyitlerinde bu söylemin dışına çıktığı ve Vâsûht tarzıaşka yaklaştığı görülür. Bu makalede Nedim’in bu tarz şiirleri ve beyitleri ele alınacak ve Vâsûht tarzıaşkın onun şiirlerinde ne şekilde ortaya çıktığı incelenecektir.

The important subjects of the love concept of the Diwan poetry which are the lover and the loved_x000D_ appears in front of us with different several features in poetry. In Diwan poetry world, there is a lover_x000D_ type who is against the loved who is described with the words of “throne, sultan, shah” and is_x000D_ victimized her lovers by tyrannizing consistently and bounded to the loved with one-sided love and_x000D_ standing to her tranny and moreover takes pleasure from this. However, there are some changes_x000D_ occur in this kind of love concept which is dominant in poetry, especially in the post-classical period;_x000D_ it is beginning to appear a lover type who does not want to stand the lovers pain and turning away_x000D_ from her. In this change which is in the concept of love in diwan poetry, the effects of the “Vasuht”_x000D_ kind of love which is developed in 16th century Persian Literature, attracts attention. To the “Vasuht”_x000D_ kind of love concept which appears in front of us as not standing the pain of the Loved, hating from_x000D_ her and turning away from her, is encountered in poems of the classic period poets, from time to time._x000D_ However, it can be said that this kind of love concept appears in front of us more clearly in diwan poetry especially afterward 18th century. One of the poets who includes “Vasuht” kind of love concept_x000D_ in his poems is Nedim. His poems mostly include the loveds and topics from real life and the_x000D_ understanding in these poems mostly overlaps with the dominant discourse in diwan poetry._x000D_ However, it is seen that in some poems and couplets of the poet he goes out of this discourse and_x000D_ approaches to “Vasuht” kind of love. In this paper, it will be dealt with this kind of poems and couplets_x000D_ of Nedim and will be studied how the “Vasuht” kind of love emerges in his poems.
‘Vasuht’ kind of love in Nedim’s poems